Validity and Reliability of Physics Learning Devices Based on Guided Inquiry to Improve Students' Creative Thinking Skills - Fikri Akbar; Ni Nyoman Sri Putu Verawati; Wahyudi (International Journal of Contextual Science Education, 2025)
This study aims to develop guided inquiry-based physics learning devices to enhance students’ creative thinking skills. The development model used is the 4D model (Define, Design, Develop, and Disseminate) developed by Thiagarajan, Semmel, and Semmel. The learning devices developed include teaching modules, learning materials, student worksheets (LKPD), and evaluation instruments. The validity and reliability of the devices were analyzed through assessments by six validators, consisting of three expert lecturers and three practicing teachers. The validation results indicated that all developed learning devices fall into the "highly valid" category, with average scores ranging from 3.32 to 3.71. The validity covered aspects of content and construct. Meanwhile, the reliability test was carried out using the Borich method, with a percentage of agreement criterion of ≥ 75%. The analysis results showed that all learning devices had reliability levels above 88%, thus categorized as reliable. It can therefore be concluded that the guided inquiry-based physics learning devices developed are feasible to be used in learning activities to facilitate and enhance students' creative thinking skills.